Women with double primary cancers of the colorectum and endometrium: do they have Lynch syndrome?. (April 2016) - Song, Taejong; Kim, Min Kyu; Lee, Yoo-Young; Choi, Chel Hun; Kim, Tae-Joong; Lee, Jeong-Won; Bae, Duk-Soo; Kim, Byoung-Gie
Abstract: Objective: The aim of this study was to determine the clinical characteristics of women with double primary cancers of the colorectum and endometrium and assess the probability of Lynch syndrome. Study design: We identified 15 women with paraffin-embedded blocks available who were diagnosed, treated and followed for double primary colorectal and endometrial cancers at in a single institution between 1994 and 2014. If there was a family history that met the revised Amsterdam criteria for Lynch syndrome, the woman was considered to have 'clinically defined Lynch syndrome'. If immunohistochemical (IHC) loss of expression of mismatch repair genes ( MLH1, MSH2, MSH6, or PMS2 ) or high microsatellite instability (MSI) was demonstrated in molecular testing, the case was considered 'suspected Lynch syndrome'. Results: The incidence of clinically defined Lynch syndrome according to the revised Amsterdam criteria was 66% (8 of 15). All 8 of the women clinically diagnosed with Lynch syndrome had either abnormal IHC loss or MSI-high, indicating a suspected Lynch syndrome. Furthermore, 27% (4 of 15) experienced second primary colorectal cancer or other Lynch syndrome-related cancers. Overall, 66% (10 of 15) met the criteria for clinically defined Lynch syndrome or suspected Lynch syndrome. Conclusions: Based on our findings, a large percentage (66%) of women with double primary cancers of the colorectum and endometrium are likely to be diagnosed with Lynch syndrome.